2007
DOI: 10.1080/02841860701403020
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with increased breast cancer-related lymphedema volume

Abstract: Early diagnosis and management of lymphedema, weight control and advices to avoid cellulitis are the main controllable parameters in women to prevent severity of breast cancer-related lymphedema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
2
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 16 publications
3
47
2
7
Order By: Relevance
“…Two recent studies complemented our study by reporting significantly less severe lymphedema among patients with BCT than with RM, all referred for treatment of lymphedema [17,18]. A non-comparative study reported a prevalence of 11% lymphedema in a BCT group with a treatment program similar to ours [19].…”
Section: Discussionmentioning
confidence: 41%
“…Two recent studies complemented our study by reporting significantly less severe lymphedema among patients with BCT than with RM, all referred for treatment of lymphedema [17,18]. A non-comparative study reported a prevalence of 11% lymphedema in a BCT group with a treatment program similar to ours [19].…”
Section: Discussionmentioning
confidence: 41%
“…This method demonstrated excellent inter-and intra-observer reproducibility in comparison to water displacement which is considered the gold standard. [7][8][9] Participants, whose volume difference between the two arms was ‡5%, were considered as lymphedema-positive patients. Patients who had 5%-10%, 10%--20%, and ‡20% volume differences between two arms were considered as mild, moderate, and severe lymphedema.…”
Section: Methodsmentioning
confidence: 99%
“…O risco para o aparecimento do linfedema está associado à dissecção e radioterapia axilar, obesidade, extensão da técnica cirúr-gica, infecção 5,9 , idade, número de linfonodos dissecados, número de linfonodos positivos e nível de retirada dos linfonodos 10 .…”
Section: Introductionunclassified